(untitled) - Crane, Stephen (Washington, D.C., 2005)
This book uses 2000 English words. Some words in the book are above this step and will be found written in boldface letters. They are explained in the glossary at the back.
Keywords: English language,English language,Tiếng Anh,Tiếng Anh,Tiếng Anh; Readers,Dạy và học,Người đọc,Study and teaching,Study and teaching